As Technophobia Disappears: Implications for Design - Grudin, Jonathan; Counts, Scott (Association for Computing Machinery, Inc., 2005)
We conducted two studies of communication: an ethnographic study of communication primarily in homes, cars, and public places, and a survey of communication in a large corporation. A clear pattern emerged. To a greater degree than expected in the ethnographic study, people were familiar with a broad range of communication tools. Awareness and a lack of anxiety was the norm even for tools that a person rarely or had not yet used. As a result, people frequently shifted to the tool that was most appropriate for a task at hand. The resulting behaviors conflict with popular press images and have implications for the designers of communication tools.